2017
DOI: 10.1093/mnras/stx1883
|View full text |Cite
|
Sign up to set email alerts
|

How fast is mass segregation happening in hierarchically formed embedded star clusters?

Abstract: We investigate the evolution of mass segregation in initially sub-structured young embedded star clusters with two different background potentials mimicking the gas. Our clusters are initially in virial or sub-virial global states and have different initial distributions for the most massive stars: randomly placed, initially mass segregated or even inverse segregation. By means of N-body simulation we follow their evolution for 5 Myr. We measure the mass segregation using the minimum spanning tree method Λ MSR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Studies of clusters' formation and very early evolution have shown that clusters can emerge from these evolutionary phases with dynamical properties characterized by mass segregation, internal rotation, and radial anisotropy in the velocity distribution; the detailed role of different dynamical processes acting during these phases and the variety of different dynamical paths resulting in these dynamical properties are still matter of intense investigation (see e.g. Goodwin & Whitworth 2004, McMillan et al 2007, Allison et al 2009, 2010, Moeckel & Bonnell 2009, Fujii et al 2012, Fujii & Portegies Zwart 2016, Vesperini et al 2014, Parker et al 2016, Domínguez et al 2017, Mapelli 2017, Banerjee & Kroupa 2014, 2017, Sills et al 2018, Daffern-Powell & Parker 2020, Ballone et al 2020, Ballone et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of clusters' formation and very early evolution have shown that clusters can emerge from these evolutionary phases with dynamical properties characterized by mass segregation, internal rotation, and radial anisotropy in the velocity distribution; the detailed role of different dynamical processes acting during these phases and the variety of different dynamical paths resulting in these dynamical properties are still matter of intense investigation (see e.g. Goodwin & Whitworth 2004, McMillan et al 2007, Allison et al 2009, 2010, Moeckel & Bonnell 2009, Fujii et al 2012, Fujii & Portegies Zwart 2016, Vesperini et al 2014, Parker et al 2016, Domínguez et al 2017, Mapelli 2017, Banerjee & Kroupa 2014, 2017, Sills et al 2018, Daffern-Powell & Parker 2020, Ballone et al 2020, Ballone et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the value of the SFE, initial cluster radii, the time-scale of gas expulsion and the degree of primordial mass segregation are subject to ongoing research (e.g. Er et al 2013;Kuhn et al 2014;Banerjee & Kroupa 2015;Megeath et al 2016;Spera & Capuzzo-Dolcetta 2017;Domínguez et al 2017;Pfalzner 2019;Kuhn et al 2019;Dib & Henning 2019;Pang et al 2020). Some of the cluster initial conditions are interrelated: for example, embedded star clusters cannot form with sub-parsec scales and SFE close to 100% because they would not be able to expand to their observed sizes (Banerjee & Kroupa 2017).…”
Section: The Influence Of the Initial Conditions Of Star Clustersmentioning
confidence: 99%
“…Broadly, real star clusters are categorised into two types based on their structure: (i) Centrally condensed type star clusters, and (ii) Hierarchical-type clusters. The structure of a cluster is related to the underlying star formation mechanisms at work (Lada & Lada 2003;Gutermuth et al 2005;Dominguez et al 2017). Centrally-condensed type of clusters usually have a single prominent peak and show highly concentrated surface density distributions with relatively smooth radial profiles, whereas hierarchical-type clusters display evidence of clustering over a large area and contain multiple peaks.…”
Section: Simulated Clustersmentioning
confidence: 99%